When to Sell Your Idea: Theory and Evidence from the Movie Industry - Luo, Hong (Management Science, 2014)
I study a model of investment and sale of ideas and test its empirical implications using a novel data set from the market for original movie ideas. Consistent with the theoretical results, I find that buyers are reluctant to meet unproven sellers for early-stage ideas, which restricts sellers to either developing the ideas fully (to sell them later) or abandoning them. In contrast, experienced sellers can attract buyers at any stage, and they sell worse ideas sooner and better ideas later. These results have important managerial implications for buyers and sellers and show that, in such contexts, policy interventions that discourage buyer participation—such as stronger intellectual property protection—may diminish the market for ideas and hurt inexperienced sellers. This paper was accepted by Bruno Cassiman, business strategy.